PREDATORY PRICING AS A TYPE OF EXCLUSIONARY ABUSE OF DOMINANT POSITION IN CASE LAW OF COURTS OF EUROPEAN UNION - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
It is quite difficult to delineate competition on merits and predatory pricing. A dominant undertaking engages in predatory conduct by deliberately incurring losses or foregoing profits in the short term in order to foreclose or be likely to foreclose one or more of its actual or potential competitors with a view to strengthen or maintain its market power. This represents an exclusionary abuse and pricing practice intended to eliminate actual or potential competitors. The abuse is exercised on the market in which the undertaking holds a dominant position. Predatory strategy comprises of two phases. In the first phase, referred to as sacrifice, the dominant undertaking reduces prices of its products to the lossmaking level. This conduct may be aimed at forcing competitors to lower their prices, incur losses and consequently, leave the market or at disciplining actual competitors or at defending from new entries of potential competitors. In the second, recoupment phase, when the goal of predation is achieved, the predator raises its prices and thereby, accumulates higher profits. This paper analyzes abuse of dominant position through predatory pricing. The author adresses views expressed in doctrine and in case law of the EU courts regarding predatory pricing.